Foreign capital in the Ukrainian banking system - Primierova, O. (Культура народов Причерноморья, 2007)
В статье проанализировано современные тенденции, преимущества и недостатки деятельности банков с иностранным капиталом. В статті проаналізовано сучасні тенденції, переваги та загрози діяльності банків з іноземним капіталом. Modern tendencies, advantages and risks of international banks' activity from the point of its influence on the financial stability of the national economy are analyzed.